The securitization of humanitarian migration [ digging moats and sinking boats - Watson, Scott D. , 1974- (Routledge advances in international relations and global politics, 2009)
Examines how western liberal states are progressively restricting access to refugees and asylum seekers, even though these states have signed international agreements obliging them to offer protection to those fleeing persecution and to advocate the spread of human rights and humanitarian principles